(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
This study assessed the suitability of River Umabolo water for irrigation based on ion concentration and water quality indices.The study sought to determine the suitability of the Umabolo river in the study area for irrigation scheme and assess the ion concentrations in the river. The water samples were collected from three points, namely; lower course, middle course and upper course. The chemical properties analyzed from the samples include sodium, calcium, potassium, magnesium, chorine, sulphate, pH, carbonate, bicarbonate, nitrate, electrical conductivity, total dissolved solids, alkalinity, salinity, boron and sodium adsorption ratio using appropriate parameters as stated in Mclean (1965). The results obtained showed the following values; 0.94 mg/l, 0.95 mg/l, 0.07 mg/l, 1.36 mg/l, 0.012 mg/l, 0.080 mg/l, 6.00, 4.85 mg/l, 4.40 mg/l, 0.10 mg/l, 0.09ds/m for Sodium, calcium, potassium, magnesium, chloride, sulphate, pH, carbonate, bicarbonate, nitrate and electrical conductivity. The total dissolved solids were 56.6mg/l while the alkalinity was 2.62mg/l. The salinity was 0.14mg/l while the sodium adsorption ratio 0.87. The study found that the water is suitable for irrigation purposes as the concentrations of the cations fall within the acceptable range for irrigation.